Per Capita Income on Poverty in Malaysia - Ilham Sentosa; Husni Muharram Ritonga (Proceeding of The International Conference on Economics and Business, 2022)
Poverty can worsen as it makes it difficult for people to fulfill their basic needs. Income is a key indicator in overcoming poverty as an increase in income can increase people's consumption levels. This study aims to examine the relationship between per capita income and the poverty rate in Indonesia. This research uses a qualitative descriptive approach by referring to literature studies that include previous research journals. The results show that, in general, per capita income has a negative relationship with the poverty rate. In other words, as per capita income increases, the poverty rate tends to decrease. The level of per capita income in a country directly affects the growth of the number of poor people in the country, as low-income levels will hinder people's ability to fulfill basic needs, maintain health, and obtain higher education.